Wave propagation and interaction with damage in periodic composite structures - Apalowo, Rilwan Kayode (2019)
A number of engineering structures such as aircraft fuselages, nuclear reactors, boilers and pressure vessels are subject to severe conditions, during operation, which can endanger the operation and lead to possible catastrophic failure. Such failure consequently has a huge impact on economy and environment. These engineering structures, especially aerospace and automotive structures, generally consist of composite materials due to their excellent mechanical properties. Therefore, there is need to develop numerical tools for constant non-destructive monitoring and assessment of composite structures in order to avoid sudden failure of these engineering components during operation. Various studies have been conducted on wave propagation, and distortion of the wave properties to examine damage/failure within structures. In the first theme of this study, a brief review of the analytical and numerical methodologies for wave propagation and interaction modelling is presented.